2014
DOI: 10.1021/jf405180k
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanin Structure Determines Susceptibility to Microbial Degradation and Bioavailability to the Buccal Mucosa

Abstract: Anthocyanins are flavonoids with reported chemoprotective activities in the oral cavity. However, information about their stability, metabolism, and tissue uptake in the mouth is limited. Anthocyanin chemical structure was recently shown to affect their stability ex vivo in saliva, and it was hypothesized that structure may affect their availability in oral tissues in vivo. Here, 12 healthy individuals retained red grape or chokeberry juice in the mouth for 5 min. Anthocyanin stability, mucus binding, and upta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 44 publications
1
34
0
Order By: Relevance
“…The complex microenvironmental parameters of the oral cavity include interaction networks between the pharmacologic agents contained in BRBs, BRB-derived metabolites, the host oral epithelium, resident bacterial biofilms, and insults such as alcohol and tobacco smoke exposure. Recently, emerging criteria have identified targetable populations demonstrating differential responses based upon oral microbiome-associated anthocyanin degradation capacities (70,71). Despite these variabilities and the intrinsic heterogeneity of cancerous lesions, 64.3% (18/28) OSCC tissues demonstrated a favorable response (reduced pro-carcinogenic gene expression) in all five molecular biomarkers in the BRB effects signature, while only 6/28 tumors showed a favorable response in ≤ 2 molecular biomarkers in the transcriptional signature.…”
Section: Discussionmentioning
confidence: 99%
“…The complex microenvironmental parameters of the oral cavity include interaction networks between the pharmacologic agents contained in BRBs, BRB-derived metabolites, the host oral epithelium, resident bacterial biofilms, and insults such as alcohol and tobacco smoke exposure. Recently, emerging criteria have identified targetable populations demonstrating differential responses based upon oral microbiome-associated anthocyanin degradation capacities (70,71). Despite these variabilities and the intrinsic heterogeneity of cancerous lesions, 64.3% (18/28) OSCC tissues demonstrated a favorable response (reduced pro-carcinogenic gene expression) in all five molecular biomarkers in the BRB effects signature, while only 6/28 tumors showed a favorable response in ≤ 2 molecular biomarkers in the transcriptional signature.…”
Section: Discussionmentioning
confidence: 99%
“…Anthocyanin aglycones are reported to have greater bioavailability glycosylated anthocyanins. Among the glycosylated anthocyanins with the same aglycone structure, varying the sugar moiety of the glycosides and the position of the same glycoside on the same anthocyanin rings affects bioavailability (Kamonpatana et al 2014;Jin et al 2011;Ichiyanagi et al 2006). The present study showed that fermentation of black carrot with either of L. plantarum or A. oryzae changed the composition of anthocyanins, such Triglyceride (mg/dL) 69.2 ± 7.4 a 58.8 ± 6.5 b 56.6 ± 6.8 b,c 52.3 ± 6.3 c 56.3 ± 7.2 à OVX-CON, OVX rats fed a high-fat diet (HFD) with 2 % dextrin; BC, OVX rats fed HFD with 2 % lyophilized water extracts of black carrot; BCAO, 2 % lyophilized water extract of black carrot fermented with Asperillus oryzae; BCLP, OVX rats fed HFD with 2 % lyophilized water extract of black carrot fermented with Lactobacillus plantarum; Sham-CON, Sham rats fed a high-fat diet (HFD) with 2 % dextrin Mean ± standard deviation (n = 10) à Significantly different from the OVX-CON by two-sampled t test at P \ 0.05 a,b Values in the same column with different superscripts were significantly different by Tukey's test at P \ 0.05…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacokinetic trial to evaluate the bioavailability of anthocyanins and colonic polyphenol metabolites after consumption of aronia berry extract in plasma and urine [96] Pharmacokinetic characterization and bioavailability of strawberry anthocyanins relative to meal intake [97] Bioavailability studies and anticancer properties of malvidin-based anthocyanins, pyranoanthocyanins and nonoxonium derivatives [98] Effect of red cabbage fermentation on anthocyanin bioavailability and plasma antioxidant capacity in humans [99] Bioavailability of red raspberry anthocyanins and ellagitannins: new insights [82] Bioavailability and uptake of anthocyanins and their metabolites from grape/blueberry juice and smoothie in vivo and in vitro [100] Tissue bioavailability and intake of tart cherry anthocyanins [101] Confirmation and identification of tart cherry anthocyanins in several target tissues of healthy rats [102] Bioactive anthocyanins in 'Queen Garnet' plum: maturity and bioavailability [103] Use of anthocyanins as bioactive colourants in lipstick formulations [104] Application of the developed flavonoid-poor menu meals to the study of the bioavailability of bilberry anthocyanins as model flavonoids [105] Anthocyanin stability, mucus binding, and uptake into epithelial cells in healthy individuals that retained red grape or chokeberry juice in the mouth [106] Absorption and bioavailability of anthocyanins across the gastrointestinal mucosa [107] Effects of processing sour cherry fresh fruit to the final juice product on the content of anthocyanins and other related polyphenols [108] …”
Section: Comments Referencesmentioning
confidence: 99%